Mannan-Binding Lectin Regulates Inflammatory Cytokine Production, Proliferation, and Cytotoxicity of Human Peripheral Natural Killer Cells - Zhou, Jia; Hu, Mengyao; Li, Jie; Liu, Yan; Luo, Jialiang; Zhang, Liyun; Lu, Xiao; Zuo, Daming; Chen, Zhengliang (Mediators of Inflammation, 2019)
Natural killer (NK) cells represent the founding members of innate lymphoid cells (ILC) and play critical roles in inflammation and the immune response. NK cell effector functions are regulated and fine-tuned by various immune modulators. Mannan (or mannose)-binding lectin (MBL), a soluble C-type lectin, is traditionally recognized as an initiator of the complement pathway. Recently, it is also considered as an immunomodulator by its interaction with kinds of immune cells. However, the effect of MBL on NK cell function remains unexplored. In this study, we found that human plasma MBL could interact directly with peripheral NK cells partially via its collagen-like region (CLR). This MBL binding markedly suppressed the interleukin-2- (IL-2-) induced inflammatory cytokine tumor necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ) production but increased the IL-10 production in NK cells. In addition, the expression of activation surface markers such as CD25 and CD69 declined after MBL treatment. Also, MBL impaired the proliferation and lymphokine-activated killing (LAK) of NK cells. Moreover, we demonstrated that MBL inhibited IL-2-induced signal transducers and activators of transcription 5 (STAT5) activation in NK cells. In conclusion, we have uncovered a far unknown regulatory role of MBL on NK cells, a new clue that could be important in the immunomodulatory networks of immune responses.